Risk assessment of workpalces for electrical energy production - Baftiu, Naim; Afrim Loku; Nadire Loku-Shehu (Technium Social Sciences Journal, 2020)
In this paper is presented the assessment of the workplace hazards for power plant "Kosova" A. The main purpose of this paper is to evaluate the work places based on the realized measurements of the conditions for safety and protection at work, classification and categorization of jobs with increased risk as well as measures for improving working conditions and preventing endangered and injured workers from injurious. Measurements of working conditions and assessment of workplace and workplace risk have been carried out by exploring, identifying, recording and analyzing any workplace in a riskiness case. With Application Software, all workplaces in which the measurements were performed are processed.